Wireless Temperature and Humidity Monitoring System for Oyster Mushroom House - Abdul Hamid, Muhammad Fakhruddin; Ahmad Nizam, Ahmad Haziq; Ismail, Farhan Nur Aiman; Ismail, Muhammad Faizal (Multidisciplinary Applied Research and Innovation, 2024)
Oyster mushrooms thrive in conditions that are dark, cool, and humid. Oyster mushrooms are simple to grow and require only a small amount of space. Regardless, mushroom cultivation requires specific growing conditions such as temperature and humidity. Because mushrooms do not require direct sunlight, temperature and humidity are two parameters that must be carefully monitored during cultivation. As a result, the creation of a wireless monitoring system for mushroom houses is required. Using the ESP8266 WiFi module, this monitoring system will monitor the temperature and humidity of the mushroom house, and an IoT dashboard will display the sensors' readings. The mushroom house's temperature and humidity are measured using DHT11 temperature and humidity sensors. The ESP8266 is outfitted with a 12V water pump to take corrective action to keep the mushroom house's temperature and humidity below 25°C and 80 percent, respectively. A Blynk dashboard will notify the oyster mushroom grower of the mushroom house's temperature and humidity. The development of this wireless temperature and humidity system will benefit farmers by enhancing oyster mushroom production and yielding better oyster mushrooms